THE ROLE OF FATHERS IN EARLY CHILDHOOD EDUCATION (PAUD) FOR PAUD TEACHERS IN SUKAMARA DISTRICT - Sari, Vera Novita (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
Early Childhood Education (PAUD) plays a vital role in a child's development, as it is during this stage that they acquire essential foundational skills that shape their future growth. However, while mothers are often the primary focus in child education, the significant contribution of fathers in supporting early childhood learning tends to be overlooked. This counseling aims to educate PAUD teachers about effective strategies in involving fathers in early childhood education. This community service activity, conducted on June 15, 2024, at the MTsN Sukamara building, used the counseling method to educate PAUD teachers on the importance of fathers' roles in early childhood development. Attended by 20 out of 45 invited teachers, the session measured knowledge improvement through pre-test and post-test evaluations. The counseling successfully enhanced PAUD teachers' knowledge in Sukamara Regency about the role of fathers in early childhood education, as indicated by an average score increase of 2.75 points. To reinforce this understanding, follow-up sessions and program expansion to other areas with tailored materials are recommended.